External and internal structure of Atta bisphaerica Forel (Hymenoptera: Formicidae) nests - Moreira, A. A. [UNESP]; Forti, L. C. [UNESP]; Boaretto, M. A C; Andrade, A. P P [UNESP]; Lopes, J. F S [UNESP]; Ramos, V. M. [UNESP] (Wiley, 2004)
This work was carried out to determine the internal and external structures of Atta bisphaerica (Forel) nests. Six nests were excavated and during excavation, all data referring to chambers and tunnels were recorded. Three nests had been internally cement-moulded, which enabled a better view of the chamber and tunnel structures. Atta bisphaerica nests presented a similar structural pattern, varying only in the number of chambers as a function of external mound area. Chambers were spherical with two communication tunnels. Internal tunnels had an elliptical section, sometimes circular, indirectly linked to chambers through ramifications and directly through short tunnels. Entrance holes were linked to the area of highest chamber concentration by tunnels from the elliptical section, which led to the nest in a radial manner. Knowledge of the colony's three-dimensional architecture permits successful application of chemical control processes, reduces the quantity of product applied, and consequently diminishes costs and environmental damage.
Keywords: Chemical control; Foraging tunnels; Grass-cutting ants; Internal architecture; Nest structure; ant; chemical control; nest structure; pest control; Atta; Atta bisphaerica; Formicidae; Hymenoptera